Hxt1, a monosaccharide transporter and sensor required for virulence of the maize pathogen Ustilago maydis. Issue 3 (10th February 2015) - Schuler, David; Wahl, Ramon; Wippel, Kathrin; Vranes, Miroslav; Münsterkötter, Martin; Sauer, Norbert; Kämper, Jörg
Summary: The smut Ustilago maydis, a ubiquitous pest of corn, is highly adapted to its host to parasitize on its organic carbon sources. We have identified a hexose transporter, Hxt1, as important for fungal development during both the saprophytic and the pathogenic stage of the fungus. Hxt1 was characterized as a high‐affinity transporter for glucose, fructose, and mannose; ∆hxt1 strains show significantly reduced growth on these substrates, setting Hxt1 as the main hexose transporter during saprophytic growth. After plant infection, ∆hxt1 strains show decreased symptom development. However, expression of a Hxt1 protein with a mutation leading to constitutively active signaling in the yeast glucose sensors Snf3p and Rgt2p results in completely apathogenic strains. Fungal development is stalled immediately after plant penetration, implying a dual function of Hxt1 as transporter and sensor. As glucose sensors are only known for yeasts, 'transceptor' as Hxt1 may constitute a general mechanism for sensing of glucose in fungi. In U. maydis, Hxt1 links a nutrient‐dependent environmental signal to the developmental program during pathogenic development. Abstract : See also the Commentary by Jan Schirawski